2012
DOI: 10.2478/v10059-012-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

How to measure motivation to change risk behaviours in the self-determination perspective? The Polish adaptation of the Treatment Self-Regulation Questionnaire (TSRQ) among patients with chronic diseases

Abstract: The aim of this study was to validate the Polish adaptation of the Treatment Self-Regulation Questionnaire (TSRQ; Ryan, Conell, 1989), which measures the degree of self-determination in risk behaviour changes (diet, exercise and smoking). The study comprised 219 patients (101 after acute coronary syndrome and 118 with type 2 diabetes), beginning to undergo treatment. The Global Motivation Scale was used to test a convergent validity. The confirmatory factor analysis (CFA) did not support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The tested 19-items TSRQ-P in this study indicated robust psychometric properties in both the emerged 4factor and 2-factor models and the conducted CFA's outputs replicated the underlying factor structure of the TSRQ demonstrated in previous studies (1,(6)(7).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The tested 19-items TSRQ-P in this study indicated robust psychometric properties in both the emerged 4factor and 2-factor models and the conducted CFA's outputs replicated the underlying factor structure of the TSRQ demonstrated in previous studies (1,(6)(7).…”
Section: Discussionsupporting
confidence: 79%
“…The original scale was validated for use in other languages i.e. English (1) Polish (7), Portuguese (10) French (44), Spanish (6), and Hungarian (45) and validity corroboration of the TSRQ-P adds to the overall functionality of the TSRQ.…”
Section: Discussionmentioning
confidence: 99%
“…(1989) theory of planned behavior. [ 36 37 ] The transtheoretical model of change,[ 24 31 ] 3D model of motivation for change,[ 25 ] stages-of-change model of motivation,[ 18 ] and social constructivist metatheory[ 30 ] were other theories that had been used to define motivation. Intrinsic and extrinsic terminology was used in the tools according to SDT.…”
Section: Resultsmentioning
confidence: 99%
“…Most questionnaires had been designed and suited in countries with English language and culture. [ 15 17 19 24 26 27 29 32 33 34 35 38 40 41 42 43 44 ] Studies in other cultures were limited to the Dutch,[ 12 14 16 17 18 31 36 37 ] German,[ 20 ] Polish,[ 37 ] Chinese,[ 28 ] Italian,[ 25 ] Swedish,[ 11 30 ] and Iranian cultures. [ 39 ] Definition of motivation: The definition of motivation varied considerably in different studies [Tables 2 and 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that varied across the multiple versions of the questionnaire is associated with the amotivation subscale, which was eliminated in several versions of the questionnaire (Denman et al, 2016;Marques et al, 2012). However, this subscale tends to be used when the Revista de Enfermagem Referência 2020, Série V, nº2: e19069 DOI: 10.12707/RIV19069 analyzed behaviors are associated with the initiation or maintenance of a medical treatment (Życińska, Januszek, Jurczyk & Syska-Sumińska, 2012). In view of the above, this study used the four-factor version: Autonomous Motivation, External Regulation, Introjected Regulation and Amotivation.…”
Section: Introductionmentioning
confidence: 99%